Sustainable management of globally significant endemic ruminant livestock in West Africa: Guidelines for the replication and improvement of the N’Dama cattle breeding program of The Gambia - Marshall, Karen; Dempfle, L. (International Livestock Research Institute, 2013)
This document is designed to assist countries partnered to the project ‘Sustainable Management of Globally Significant Endemic Ruminant Livestock in West Africa’ (PROGEBE www.progebe.net) in the development of plans for N’Dama cattle within breed improvement programs, following the 3-tier (nucleus/multiplier/ commercial) model of The Gambia. The document proceeds as follows. First some background information is given including the broad steps to developing an animal breeding program (based on FAO 2010), as well as a basic overview of a 3-tier breeding program. Second, The Gambia breeding program is described from both a historical perspective and in terms of its current activities. Third, detailed guidelines are given in relation to the replication/improvement of the breeding program, with a number of specific recommendations made. Finally issues which will be critical to the success of the program—including human capacity, breeding program sustainability, and scale of operation—are discussed in some detail. It should be noted that underlying assumptions to this document are that a) within-breed genetic improvement of N’Dama cattle is an appropriate livestock development intervention within the PROGEBE countries, and that b) the 3-tier model of The Gambia is the most appropriate genetic improvement and dissemination model to implement. This document does not discuss these issues further, as it is understood that the PROGEBE country partners are already committed to establishing such breeding programs. It should also be stressed that this document does not replace the need for country-level capacity in terms of trained people for genetic improvement programs to design and oversee their N’Dama breeding activities. Instead this document should be considered reference material, from which the country-level animal breeders/ quantitative geneticists and other stake-holders can draw on in designing their specific breeding plans.